The Importance Training of Statistics and the Probability Theory in the General Education School within the Framework of the Updated Education Content (Journal of Educational Sciences, 2018)
The article deals with the issue of the transition of Kazakhstan secondary education to the updated content and relevance of the study of probability theory and mathematical statistics with the aim of improving the quality of education of schoolchildren in general education institutions. The modern concept of school mathematics education is focused, first of all, on the account of the individuality of the child, his interests and inclinations. This determines the selection criteria for content, the development and implementation of new, interactive teaching methods, changes in the requirements for the student’s mathematical preparation. And from this point of view, when it comes not only to teach mathematics,but also to form a personality with the help of mathematics, the need for development of probabilistic intuition and statistical thinking in all students becomes an urgent task.Moreover, today we are talking about the study of probabilistic and statistical material in the compulsory basic school course «mathematics for all» within the framework of an independent content-methodical line throughout all the years of study. The authors of the article consistently reveal the importance of teaching probability theory and mathematical statistics and cites the main applications of these sections of mathematics in various fields of activity. In conclusion, the authors emphasize the relevance of teaching the course of probability theory and mathematical statistics in the general education school.Key words: general education school, statistics, probability theory, renewed content program.